Interactive contrasting learning styles : their impact on university student's learning orientations study skills and academic achievements - Abu, Baharin; Md. Johan, Othman; Syed Mansor Alhabshi, Syed Mohamed Shafeq (Universiti Teknologi Malaysia, 2003)
The study examines undergraduate university students’ learning styles and study skills level. A total of 310 undergraduate students of different study years and programs at the Education Faculty, Universiti Teknologi Malaysia involved in the study. The respondents comprised of 82 male and 228 female students. The study employed a set of questionnaire measuring on students’ different learning styles and study skills using four point scales. The five categories of learning styles by Dunn and Dunn are Environmental, Emotional, Sociological, Physical and Psychological. The six aspects of study skills are Referencing, Listening, Note-taking, Reading, Preparing for Examination and Managing Time. The Cronbach Alpha coefficient for the instrument is 0.83. The result showed that the students’ learning styles were mainly of Emotional category with mean score 3.09 (SD=0.63), second was Psychological category (mean 2.98, SD=0.84), third was Physical category (mean 2.87, SD=0.72), fourth was Environmental category (mean 2.81, SD=0.70) and finally, Sociological category (mean 2.81, SD=0.74). Generally, the students’ study skills level was found to be moderate. The mean score for Referencing Skill was 3.09 (SD=0.58), Listening Skill (mean 3.04, SD=0.64) and Note-taking Skill (mean 3.03, SD=0.71) were categorized as highest level. Three other skills i.e. Reading (mean 2.94, SD=0.66), Preparing for Exam (mean 2.80, SD=0.72) and Managing Time (mean 2.80, SD=0.75) were recorded at the moderate level. The different styles and study skills level adopted by students have directly influenced students’ orientations and approaches to learning. Finally, several recommendations were given to enhance students’ teaching and learning effectiveness.